2009
DOI: 10.5424/sjar/2009071-409
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different soil tillage systems and coverages on soybean crop in the Botucatu Region in Brazil

Abstract: Nowadays, agricultural practices should combine high yields with a sustainable use of resources. Different tillage practices and crop covers, if combined, may help to achieve both objectives. In this work, several traits of a soybean (Glycine max L. Merr) cultivar were studied under different conditions of tillage and previous soil coverages. The experiment was installed at Lageado Research Station, Botucatu county, SP, Brazil, on a Paleudult. It consisted of nine treatments (combining three systems of soil ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
1
5
0
1
Order By: Relevance
“…In contrast, Barrios et al (2006) observed significantly higher yields in soybean crops under conventional tillage than in no tillage system in a rotation maize/soybean. At the same time, Lança Rodrígues et al (2009) found no signifi cant differences in soybean seed yields among tillage systems. Moreover, some studies have suggested that NT can lead to reduced yields because of lower N availability (Matowo et al 1997) and greater nematode infestation (Koenning et al 1995) compared with conventional tillage system.…”
Section: Seed Yieldmentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast, Barrios et al (2006) observed significantly higher yields in soybean crops under conventional tillage than in no tillage system in a rotation maize/soybean. At the same time, Lança Rodrígues et al (2009) found no signifi cant differences in soybean seed yields among tillage systems. Moreover, some studies have suggested that NT can lead to reduced yields because of lower N availability (Matowo et al 1997) and greater nematode infestation (Koenning et al 1995) compared with conventional tillage system.…”
Section: Seed Yieldmentioning
confidence: 88%
“…1). Lança Rodrígues et al (2009) found higher values for seed number per pod under conventional and reduced tillage systems than under no tillage system. Mohammadi and Amiri (2011) reported that seed number per pod was signifi cantly lower in non-weeded plots compared to full-season weedfree plots.…”
Section: Seed Number Per Pod (Sn)mentioning
confidence: 95%
“…A ausência de resposta da escarificação sobre a produtividade da soja também foi verificada por outros autores, mesmo quando este manejo apresentou melhoria das propriedades físicas (Camara & Klein, 2005;Lança Rodrígues et al, 2009;Secco et al, 2009). O aumento da produtividade das culturas com uso da escarificação pode estar associado à quebra de camadas compactadas, o que geralmente ocorre nos primeiros anos de implantação do sistema de semeadura direta ou em áreas com manejo inadequado, com ausência de rotação de culturas.…”
Section: Resultsunclassified
“…The greatest number was seen for the conventional system (5799 pods m −2 ), with significantly lo pod numbers for the conservation and no-tillage systems (2206 and 2547 pods m −2 , res tively) (Table 2). [46] also reported that their conventional and reduced tillage sys showed greater pod numbers per plant compared to their no-tillage system. The 100mass for the conventional system (19.7 g) was significantly greater than for the conse tion and no-tillage systems, which were similar (17.3 and 16.4 g, respectively) (Tab Indeed, such tillage systems have been shown to have relevant effects on absolute mass [47], while [48] reported that their conventional system favored soybean seed (as 1000-seed mass) over their no-tillage system.…”
Section: Soybean Yield Components and Dry Seed Productionmentioning
confidence: 96%
“…Ref. [46] also reported that their conventional and reduced tillage systems showed greater pod numbers per plant compared to their no-tillage system. The 100-seed mass for the conventional system (19.7 g) was significantly greater than for the conservation and no-tillage systems, which were similar (17.3 and 16.4 g, respectively) (Table 2).…”
Section: Soybean Yield Components and Dry Seed Productionmentioning
confidence: 98%